Influence of Recovery Strategy And Rehidration upon Recovery Perception and Performance Following Fatiguing Exercise In College Students - Hadi, Risa; Harun; Wardiyanto, Yayan; Khoiriyah, Nur; Hidayat Suharto, Taufik; Nurul Akbar, Muhammad Syifa (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2026)
Regular physical exercise significantly reduces morbidity and mortality (death) by lowering risks for chronic diseases like heart disease, type 2 diabetes, and some cancers, improving mental health, and increasing overall longevity. But exercise can sometimes cause fatigue that interferes the daily activities, and the right recovery strategy can help a person recover more quickly. The purpose of this study was to analyze the effects of various recovery methods and rehydration on physical performance and recovery perception. The 36 college students (age 24,3±5,1 years, 67,6±16 kg, 166,5±5,2 cm, and VO2max 40,6±2,25 ml/kg/min) divided into six treatment groups: K1 (passive recovery, n=6), K2 (active recovery, n=6), K3 (electrolite water, n=6), K4 (green coconut water, n=6), K5 (active recovery + electrolite water, n=6), and K6 (active recovery + green coconut water, n=6). All subject underwent a fatigue protocol using the Yoyo intermittent recovery test level 1 (YYIRT1) and handgrip strength dan sprint 20m and rating perceived exertion (RPE) were measured before and after the recovery intervention to assess the effects of various types of treatment. A difference test analysis will be conducted to observe the effect of each treatment group. The results of this study indicate that there was a significant difference in the reduction of RPE (p<0,05) and the electrolyte water group showed the most significant decrease. There was no significant difference in handgrip strength and 20 m sprint parameters (p>0,05). Electrolite water significant decreasing short term perceptual recovery after high intensity training, electrolite water should be implemented after high intensity training.